2017
DOI: 10.1089/jpm.2016.0504
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Advance Care Planning Intervention in Community Settings with Older Latinos: A Feasibility Study

Abstract: Based on enrollment and intervention completion rates, time to completion tests, and feedback from qualitative post-study, follow-up interviews, the ACP-I Plan was demonstrated to be feasible and perceived as extremely helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…designed to improve ACP communication and AD documentation among older Latinos with chronic diseases. 25 The primary study used mixed data collection methods with surveys and open-ended qualitative interviews which explored satisfaction with the MI counseling program after completing a posttest. Inclusion criteria for eligible participants indicated 1 or more chronic medical conditions and excluded those diagnosed with dementia or Alzheimer disease, schizophrenia/schizoaffective disorder, or manic-depressive disorder (self-reported).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…designed to improve ACP communication and AD documentation among older Latinos with chronic diseases. 25 The primary study used mixed data collection methods with surveys and open-ended qualitative interviews which explored satisfaction with the MI counseling program after completing a posttest. Inclusion criteria for eligible participants indicated 1 or more chronic medical conditions and excluded those diagnosed with dementia or Alzheimer disease, schizophrenia/schizoaffective disorder, or manic-depressive disorder (self-reported).…”
Section: Methodsmentioning
confidence: 99%
“…Investigators previously reported our recruitment strategies elsewhere. 25 Briefly, we recruited participants from community settings in Southern New Mexico (34% medical outpatient clinics, 12% religious settings, 26% community senior centers, and 28% from general community outreach with flyers at Farmers Market, low-income housing, food banks, grocery stores, and other locations). The institutional review board at New Mexico State University approved all procedures and participants signed informed consent to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study from this research program examined the feasibility of delivering ACP education and counseling for older Latinos with advance chronic illness in community settings in Southern New Mexico using community-engaged research methods. 18 The feasibility study found that participants were satisfied with ACP education and appreciated information encouraging them to take action to document an AD and initiate patient-provider family communication to discuss plans for EOL care. 18 A second study from this research program examined experiences with ACP education and motivational intervention (MI) counseling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…18 The feasibility study found that participants were satisfied with ACP education and appreciated information encouraging them to take action to document an AD and initiate patient-provider family communication to discuss plans for EOL care. 18 A second study from this research program examined experiences with ACP education and motivational intervention (MI) counseling techniques. Delivered by social workers, the goal was to provide MI counseling to encourage ACP communication with patients and family members among older Latinos with advanced chronic diseases.…”
Section: Introductionmentioning
confidence: 99%